Ocular Ultrasonography: A Useful Instrument in Patients with Trauma Brain Injury in Emergency Service - Julie Natalie Jimenez Restrepo; Oscar Javier León; Leonardo Alexander Quevedo Florez (Emergency Medicine International)
The measurement of the optic nerve sheath by ocular ultrasonography might be an indirect method to assess the quickly increase of the intracranial pressure in patients with moderate trauma brain injury, taking into account that an important proportion of these could develop the increase of the intracranial pressure in a hospital-acquired way. Therefore noninvasive, reliable, and convenient techniques are needed making the ocular ultrasonography a useful tool, due to the invasive monitoring elements’ problems and the poor access to measure the intracranial pressure in emergency services. In spite of the limitations and few studies that exist to consider it as a possible early detection, this technique could work as a noninvasive one in the case that could not be possible to do invasive monitoring or when it is not recommended.